Does Informational Behavior in Wound Care Vary According to Professional Experience? - Silva, Bruno Santana da; Silva, Paulo Vanzolini Moura da (Informação em Pauta, 2022)
Although informational behavior of Nursing professionals has already been investigated, understanding of what influences these behaviors is still limited. Thus, this work investigated whether and how informational behavior during wound care varies according to professional experience. A descriptive quantitative research was carried out through an electronic questionnaire filled in by 566 participants between January and February 2020. Variations identified in the workplace, experience time and frequency of patient consultations follow variations in the use of sources, frequency of obtaining and in the way of recording information during wound care. The maximum variations were up to 38% in registration modes, up to 37% in use of information sources and up to 26% in frequency of obtaining desired information according to variation in professional experience reported by the participants. We concluded that information systems used to support wound care need to adequately accommodate these variations related to evolution of Nursing professionals’ experience.